Proposal to commit an indecent act in order to derive a financial benefit (Ius Novum, 2023)
The article presents the issue of a misdemeanour of proposing to commit an unlawful actin order to obtain a material benefit classified in Article 142 MC. In order to provide fullcharacteristics of the discussed type of misdemeanour, a classical pattern based on the traditionaldivision of statutory features of the type of prohibited act has been adopted. Theauthor discusses such issues as statutory penalties for this misdemeanour and concurrence ofprovisions. The article also draws special attention to issues raising doctrinal controversies,including inter alia: approach to the object of protection, the interpretation of the features of“prostitution”, “material benefit” or “other behavior violating public order”. A number ofspecific issues were also analysed, including liability under Art. 142 MC persons providingroadside sexual services.
Keywords: public decency; proposing; insistently; violation of public policy in another way; debauchery act; material benefit